Women in the Armed Resistance in the Northeast of Lithuania: The Case of the King Mindaugas Partisan Region - Staveckaitė-Notari, Ramona; Tumavičius, Andrius (Genocidas ir rezistencija, 2024)
The purpose of the article is to refine the data of the initial statistical study, “Women in the Lithuanian Partisan War, 1944-1953”, by examining the biographies of the female partisans in the Northeastern Lithuania partisan region according to targeted biographical parameters, and to present an objective picture of the female partisan. The paper analyses the reasons for women getting involved in the partisan movement, examines the social cross-section of the female fighters, and investigates the marital status and fates of the female partisans. After conducting the research, it was found that more than half of the female fighters chose this path because they had been influenced by their immediate environment, i.e. their relatives were actively involved in the armed resistance. This insight confirms the relationship between women’s motivation and the activities of their relatives imparted in historiography. One tenth of the female partisans examined became involved in the armed resistance for political reasons. This trend correlates with the insight that political engagement was low among women. Examination of the social cross-section revealed that most of the female partisans came from farming families, i.e. belonged to the main social group of the Republic of Lithuania population. Empirical data confirmed the opinion that the partisan resistance was essentially a struggle of the rural part of society against the Soviet regime. An analysis of the marital status of the female partisans revealed that more than 60 per cent of the female fighters were single, while 30 per cent were married and 18 per cent had children. The study of the fates of the female fighters imparts that these women either died/committed suicide or were arrested and convicted. There were only a few isolated cases of female partisans becoming legal. In this case, a clear difference is evident between the fates of women and men. Men became legal both individually and in groups. The Soviet repressive system treated male and female partisans equally – they were called “bandits” and punished according to Article 58 of the Criminal Code of the RSFSR.